Adsorption of Uranium onto Delaminated Amino Talc-Like Clay - Saputra, Dwi Luhur Ibnu; Purwaningsih, Henny; Farid, Muhammad; Basuki, Triyono; Nakashima, Satoru; Rachmadetin, Jaka; Laksmana, Roza Indra; Sihotang, Juan Carlos; Noerpitasari, Erlina (EKSPLORIUM, 2025)
Uranium-containing waste is generated as a by-product of nuclear power plants, radioisotope production, nuclear fuel fabrication, and mineral processing. A radioactive waste treatment plant treats radioactive liquid waste using various methods, including evaporator technology, ion exchange resins, and adsorbents. Various adsorbents have been investigated for the removal of uranium from aqueous solutions. Negatively charged adsorbents, such as natural clay, biomass-based adsorbents, and polymers, have been utilized for uranium adsorption. Previous research on uranium adsorption by amino clay, which has a positively charged surface, was still very limited compared to other adsorbents. In the present study, the application of Delaminated Amino talc-like Clay (DAC) for removing uranium from aqueous solutions was examined. DAC with amino propyl on the tetrahedral sheet surface is easily protonated to form a positively charged R-NH3 that may influence its interaction with uranium. The speciation and reaction kinetic order were studied in aqueous solution with pH and contact time as the variables. The adsorption of uranium onto DAC, which is likely due to physicochemical interactions and ion trapping, was evaluated. The maximum removal efficiency (84.5%) and adsorption capacity (113.06 mg/g) were achieved at pH 4 after approximately 60 minutes. The uranium adsorption capacity is low at pH 2 and 3 (10%), which is due to the repulsive interaction between the positive surface charge of DAC and (UO2)2+ as the dominant uranium species. Uranium adsorption capacity is high at pH 4 and 5, because the predominant species of uranium, such as (UO2)2+ and [(UO2)2(OH)2]2+, were probably adsorbed by DAC through chemisorption with R-NH2. The adsorption of uranium on the DAC was found to follow the pseudo-second order kinetic model.